2022
DOI: 10.1038/s41598-022-13496-4
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic profiles of the early life microbiome of Indonesian inpatient neonates and their influence on clinical characteristics

Abstract: Determining the initial normal neonatal gut microbiome is challenging. The debate regarding the sterile fetal environment is still ongoing. Therefore, studying and comparing normal and dysbiotic microbiomes requires the elucidation of both the fetal and infant microbiomes. Factors influencing the normal microbiome also include regional and genetic factors specific to different countries. Determining the normal microbiome population in our center and their association with the clinical conditions of infants is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Most women delivering vaginally received antibiotics for PROMs, rather than for routine surgical prophylaxis in caesarean section. A previous study found that PROMs altered the composition of the infant meconium but this disappeared 4–7 days after birth [56], so this is unlikely to be an important factor for infant gut composition at 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Most women delivering vaginally received antibiotics for PROMs, rather than for routine surgical prophylaxis in caesarean section. A previous study found that PROMs altered the composition of the infant meconium but this disappeared 4–7 days after birth [56], so this is unlikely to be an important factor for infant gut composition at 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we collected extensive data on maternal living environments and lifestyles during pregnancy, such as fish and meat consumption, leisure time spent in forests, the presence of older siblings or furry pets in the home, smoking in the home and maternal weight, and established that these prenatal factors had little effect on the microbial composition of meconium. It is therefore understandable that the prenatal factors considered in our systematic review, including maternal diet, 2 , 37 , 84 , 85 residential area, 37 , 44 age, 37 , 44 , 49 , 50 , 53 , 57 , 86 ethnicity, 3 , 49 weight, 3 , 38 , 44 , 49 , 53 , 56 , 57 , 75 , 86 smoking, 3 , 37 , 44 , 87 pregnancy-related health issues, 36 40 , 47 , 49 , 54 , 60 , 71 , 75 , 85 , 86 non-pregnancy-related health issues 3 , 37 , 38 , 44 , 45 , 49 , 70 , 76 , 88 , 89 and education, 37 , 44 , 49 together with environmental pollutants, particularly metals and microplastics 58 , 90 and the presence of furry pets 13 , 45 yielded mixed results. Another commonly studied newborn factor, which we did not analyze in our cohort study, was gestational age, 3 , 4 ...…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small number of subjects, further analyses were difficult. However, a study on 8 preterm neonates in Indonesia reported that PROM and mother’s diet influenced the meconium microbiome [ 46 ]. Further studies including a larger cohort of preterm infants are needed to make any conclusions on the impact of early exposure to vaginal microbiomes in utero and colonization and establishment of the infants’ gut microbiome.…”
Section: Discussionmentioning
confidence: 99%